분산염료/산성염료에 의한 PTT(polytrimethylene terephthalate)/견 교직물의 염색에 관한 연구 - 성우경; Woo Kyung Sung (한국의류산업학회지, 2010)
The dyeing of poly(trimethylene terephthalate)(PTT)/silk mixture fabrics can be accomplished by a two bath dyeing method with separate application of the disperse dyes on the PTT, reduction cleaning of the stained silk and then dyeing the silk with the acid dyes, or by one bath dyeing method with mixed dye ranges, possibly followed by a cleaning treatment. The two bath dyeing method has the advantage of better results with respect to dry cleaning fastness properties thanks to the possibility of an intermediate reduction clear. On the other hand, as compared with the two bath dyeing method, one bath dyeing method with a mixed dye range permits rapid and more reproducible dyeing, without the risk of great difference with respect to the shade of the strike on both substrates as well as savings of time, energy and water usage. This study was carried out to investigate dyeing characteristics of PTT/silk mixture fabrics with disperse dyes/acid dyes by one bath dyeing method in comparison with two bath dyeing method in the interests for rationalization of the dyeing process.